Counseling Teacher Collaboration And Teachers in the Implementation of Student Counseling Programs - Offando, Ocen; Ahmad, Riska; Syukur, Yarmis (Widyagogik, 2023)
Collaboration with school personnel , especially homeroom teachers, is required in implementation effective and efficient BK program . One of the advantages of school collaboration is that it makes it easier for counselors to run the counseling program. This article aims to describe the collaboration between the BK teacher and the homeroom teacher in implementing BK . The method of writing articles refers to literature reviews such as books and the results of relevant articles. The findings of the article show that there are two types of cooperation that can be carried out, the first is collaboration between the BK teacher and the homeroom teacher in carrying out counseling activities, which include (1) making notes on student events, (2) making observation reports, (3) organizing sociometry, (4) providing information about student identity, (5) conducting home visits, (6) conducting psychological tests, and (7) collecting student data. The second type of collaboration is the counseling teacher working with the homeroom teacher to provide information about students in terms of: (1) attendance data, (2) absence data, and (3) data on student delays in coming to school.